2010
DOI: 10.17221/160/2009-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

The effects of butylated hydroxyanisole, ascorbic acid, and α-tocopherol on some quality characteristics of mechanically deboned chicken patty during freeze storage

Abstract: Ozer O., Sariçoban C. (2010): The effects of butylated hydroxyanisole, ascorbic acid, and α-tocopherol on some quality characteristics of mechanically deboned chicken patty during freeze storage. Czech J. Food Sci., 28: 150-160.In this study, the effects were evaluated of butylated hydroxyanisole (BHA), ascorbic acid (AA) and α-tocopherol (TO) on the stability of raw mechanically deboned chicken patties stored at -20°C for 6 months. pH, thiobarbituric acid reactive substance (TBARS), haem iron (mg/kg), metmyog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 40 publications
3
29
0
1
Order By: Relevance
“…Ramzan (1998) reported that the TBAV of broiler feeds increased with storage time. The findings of the current study support the results of Ozer & Sarcoban (2010) that the application of an antioxidant decreased the TBAV of mechanically-deboned chicken patties to permissible limits. In the untreated PBPM batch (A), the determined TBAV was higher (3.20 mg MDA/kg) on day 42than the safety limits recommended by the Egyptian Standards (ES, 2005), which states that TBAV of ≥ 0.9 mg MDA/kg of a product at any given time is sufficient to consider it rancid.…”
Section: Discussionsupporting
confidence: 89%
“…Ramzan (1998) reported that the TBAV of broiler feeds increased with storage time. The findings of the current study support the results of Ozer & Sarcoban (2010) that the application of an antioxidant decreased the TBAV of mechanically-deboned chicken patties to permissible limits. In the untreated PBPM batch (A), the determined TBAV was higher (3.20 mg MDA/kg) on day 42than the safety limits recommended by the Egyptian Standards (ES, 2005), which states that TBAV of ≥ 0.9 mg MDA/kg of a product at any given time is sufficient to consider it rancid.…”
Section: Discussionsupporting
confidence: 89%
“…As data analysis shows, the efficiency of lipid oxidation reduction in our study was statistically influenced by the interaction of PEO concentration and storage time (P-value<0.05). These findings concord with previous results that the synergistic effects of the used antioxidants and storage time modulated the lipid oxidation rate (McKibben and Engeseth 2002;Ozer and Saric¸ObaN 2010;Radha krishnan et al 2014).…”
Section: Analysis Of the Mdcm Samples Marinated With Peosupporting
confidence: 92%
“…A decrease in the a * value is reportedly associated with the effects of pH on the myoglobin proportion. A decrease in the a * value during cold storage has been suggested in previous reports to be attributed to the oxidation of oxymyoglobin to metmyoglobin …”
Section: Resultsmentioning
confidence: 59%